Update breast cancer 2022: Part 1: Early stage breast cancer - Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Evidence relating to the treatment of breast cancer patients with early-stage disease has increased significantly in the past year. Abemaciclib, olaparib, and pembrolizumab are new drugs with good efficacy in the relevant patient groups. However, some questions remain unanswered. In particular, it remains unclear which premenopausal patients with hormone receptor-positive breast cancer should be spared unnecessary treatment. The question of the degree to which chemotherapy exerts a direct cytotoxic effect on the tumor or reduces ovarian function through chemotherapy could be of key importance. This group of patients could potentially be spared chemotherapy. New, previously experimental biomarker analysis methods, such as spatial analysis of gene expression (spatial transcriptomics) are gradually finding their way into large randomized phase III trials, such as the NeoTRIP trial. This in turn leads to a better understanding of the predictive factors of new therapies, for example immunotherapy. This review summarizes the scientific innovations from recent congresses such as the San Antonio Breast Cancer Symposium 2021 but also from recent publications.
Gesehen am 19.01.2023